PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MUSLIM DI 212 MART BANDA ACEH - Siti Paradita Saprina Boru Matondang; T. Meldi Kesuma (Departemen Manajemen, 2020)
This study aims to measure the effect of store atmosphere on purchasing decisions of Muslim consumers at 212 Mart Banda Aceh. The sample used in this study was the people of Banda Aceh city who made a purchase or visited 212 Banda Aceh Mart, totaling 170 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is accidental sampling. Multiple Linear Regression is used as a method of analysis to determine the effect of all the variables involved. The results showed that partially cleanliness variables influence purchasing decisions, music has no influence on purchasing decisions, scents affect buying decisions, temperature does not affect purchasing decisions, lighting influences buying decisions, color has no effect on buying decisions, display/layout influences on buying decisions, and that simultaneously cleanliness, music, scent, temperature, lighting, color, and display/layout affect the purchase decision.